Greenfield's surgery : scientific principles and practice - 4 0 16; 1934- Greenfield, Lazar J.,;Mulholland, Michael W.; 5 (Philadelphia, PA : Lippincott Williams & Wilkins, 2006)
The classic surgery text edited by Lazar Greenfield, Michael Mulholland, and colleagues is in its new Fourth Edition thoroughly revised by a new editorial team and now illustrated in full color throughout. The book provides comprehensive coverage of all types of surgery and continues Greenfield's widely acclaimed tradition of integrating basic science with clinical practice. This edition has three new editors cancer specialist Gerard Doherty, trauma/critical care specialist Ronald Maier, and vascular surgeon Gilbert Upchurch, Jr. Coverage of cancer and trauma surgery has been greatly expanded and new chapters on vascular diagnostics, endovascular treatment of disease, and venous disease have been added.
Oldham --;Robert E. Cilley and Peter W. Dillon --;Thomas T. Sato and Keith T. Oldham --;Eugene Minevich and Curtis A. Sheldon --;Michael P. LaQuaglia --;H. David Moehring --;Jean-Christophe Leveque and Julian T. Hoff --;David Y. Chan, Arthur L. Burnett, Ronald Rodriguez, and Thomas W. Jarrett --;Robert L. Giuntoli II, Geoffrey Cundiff, and Robert E. Bristow --;N. Scott Adzick and Alexander S. Krupnick --;Alfred E. Chang, Timothy M. Johnson, and Amy Kim Gira --;Michael S. Sabel --
Rev. ed. of: Surgery. 3rd ed. 2001.
Includes bibliographical references and index.
Keywords: 2 -- 0; 6; Surgery.;Medicine.;General Surgery.;Surgical Procedures, Operative. -- 20; 20; 2